E-243 Flow diversion of cerebral aneurysms in type IV osteogenesis imperfecta: a report of the first two treatments in humans. (23rd July 2022) - Zarrin, D; Campos, J; Meyer, B; Golshani, K; Beaty, N; Bender, M; Colby, G; Lin, L; Coon, A
Abstract : Background: Osteogenesis Imperfecta (OI) is a heritable collagen synthesis disorder which predisposes individuals to numerous maladies including easy bone fracture, vessel fragility, and platelet dysfunction. We report the first known case of neurointerventional treatment with flow diversion embolization of intracranial aneurysms in a patient with OI. Methods: We identified a patient in our IRB-approved prospective cerebrovascular database with OI and reviewed pertinent demographic information, medical history, aneurysm type, procedural details, periprocedural events and angiographic follow-up. Results: A 60-year-old woman with known OI type IV, history of 46 lifetime bone fractures and hypertension, underwent workup for transient ischemic attacks revealing a 4-mm anterior cerebral artery (ACA) aneurysm along the right A1 segment in 2016. Perioperative dual antiplatelet therapy was aspirin 81 mg and clopidogrel 75 mg daily. A tri-axial catheter access system consisting of a guide catheter (Infinity), distal access catheter (Catalyst 5), and a microcatheter (Via27) over a guidewire was utilized to deploy a 3.5 x 16 mm Pipeline Flex Embolization Device, jailing the right middle cerebral artery (MCA). There were no perioperative complications. Two-month clinical and angiographic follow-up revealed Raymond I obliteration of the aneurysm with robust ACA pial collateralization to the MCA territory. Five-year follow-up angiography revealed a de novo left-sided 3-mm A1-A2 junction saccular aneurysm and stable right MCA collateralization. Flow diversion embolization of the de novo aneurysm consisted of a triaxial system with a guide catheter (Tracstar), distal access catheter (Catalyst 5) plus delivery assist catheter (Offset), and a microcatheter (XT27/SL10) over a guidewire. A guidewire exchange was utilized to navigate the tortuous distal ICA segments. A 4 x 12 mm Surpass Evolve flow diverter was successfully deployed in the 1.5-mm diameter parent vessel. There were no perioperative complications. Six-month clinical and angiographic follow-up revealed Raymond I aneurysm obliteration. Conclusion: Endovascular flow diversion as a treatment modality can offer safe and curative reconstruction of intracranial aneurysms in patients with osteogenesis imperfecta. Disclosures: D. Zarrin: None. J. Campos: None. B. Meyer: None. K. Golshani: None. N. Beaty: 2; C; Proctor for Medtronic Neurovascular, Stryker Neurovascular, CMO of NeuroMedica. M. Bender: None. G. Colby: 2; C; Consultant for Medtronic Neurovascular, MicroVention-Terumo, Stryker Neurovascular. L. Lin: 2; C; Consultant/Proctor: Medtronic Neurovascular, Stryker Neurovascular, MicroVention-Terumo, Rapid Medical, Bolt. A. Coon: 2; C; Consultant/Proctor: Avail MedSystems, Imperative Care, InNeuroCo, Medtronic Neurovascular, MicroVention-Terumo, Q'apel, Rapid Medical, Stryker Neurovascular, Sequent Medical.